Removal of Coloured Impurities from Caprolactam Solution by Adsorption onto Activated Carbon: Equilibrium and Thermodynamic Studies - Hongtao Zhang; YunBai Luo; Ping Yu; Zhen Yuan (Adsorption Science & Technology)
A large number of impurities appear during the production of caprolactam. Such impurities — especially coloured impurities — having a maximum UV absorbance at a wavelength of 290 nm, make it quite difficult to isolate the high-purity product. In order to improve the purification technology, the removal of the coloured impurities from caprolactam solution by adsorption onto activated carbon was studied with good results. The thermodynamic and mass-transfer behaviours of the adsorption process were also examined in this study with the values of D i , k id , E a and E # being calculated. The magnitudes of the thermodynamic parameters ΔG 0 , ΔH 0 and ΔS 0 were also evaluated. A negative ΔG 0 value confirmed the feasibility of the method and the spontaneous nature of the adsorption process. The positive value of ΔH 0 indicated the endothermic nature of the process while the positive value of ΔS 0 indicated an increase in the degrees of freedom of the adsorbed species. The value of ΔH iso increased with the extent of adsorption and showed a linear relationship when plotted against ln q.